The Effect of English British Council Site on Students’ English Vocabulary at Eight Grade SMPN 02 Bangkalan - Baqiyatus Sholihah; Wijaya, Mohammad Kurdi (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2020)
Vocabulary is one of important aspect in learning English. For second language students, it is a new challenge to master it. Since, they have vocabulary of their own native language. They have to compare it and replace something new to their understanding. Some vocabularies are similar and some vocabularies are completely different. Therefore, an attractive medium is needed to make students interest to master vocabulary. English British Council Site is applied on this experiment. This research is quantitative pre- experimental research with one group pre-test post-test design. It is aimed to measure the effectiveness of using the English British Council site toward the students mastering vocabulary. Forty students are involved on this experiment. The result shows significant different of pre-test and post-test. It indicates the using of British Council Site is effective to be used for students’ second language to master the vocabulary.